Seismic yield displacement of reinforced concrete bridge pier columns in saline soil environment. Issue 12 (September 2019) - Yan, Changwang; Zhao, Jianjun; Liu, Shuguang; Zhang, Ju
Corrosion of bridge pier columns in saline soil environment is inevitable, resulting in a gradual decrease in seismic yield displacement. In this study, 10 reinforced concrete bridge pier columns were fabricated, and seismic yield displacement in the saline soil environment was studied. Electrochemical corrosion tests and low-cycle repeated loading tests were carried out. The axial compression ratio and corrosion rate are the main parameters considered in this article. The seismic yield displacement test value of the pier column is determined based on the energy method. Using the static method, the theoretical expression of the earthquake yield displacement is derived. According to our results, when the corrosion rate is constant, the axial compression ratio is within a certain range, and the seismic yield displacement of the pier increases with the increase in the axial compression ratio. Similarly, when the axial compression ratio is constant, the seismic yield displacement decreases as the corrosion rate increases. By comparing experimental results with calculation results, our mathematical expressions have been shown to be effective in predicting seismic yield displacements of pier columns at different times in saline soil environments.